IMPLEMENTASI MODEL METODE GERAK DAN LAGU DALAM MENGHAFAL ASMAUL HUSNA BAGI ANAK USIA DINI: (Studi Pada TK Pertiwi Dharma Wanita Palengaan Pamekasan) - Laila, Khorridatul; Farida, Siti (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2023)
Implementation of the motion method model and deep songmemorize Asmaul husna (Ø§Ù„ØØ³Ù†Ù‰ Ø§Ù„Ø§Ø³Ù…Ø§Ø¡) for early childhood is an important aspect in the dynamics of education and teaching systems. The findings of field research conducted by research show that the implementation of the Movement and Song method models in memorizing Asmaul Husna (Ø§Ù„ØØ³Ù†Ù‰ Ø§Ù„Ø§Ø³Ù…Ø§Ø¡) is an effort taken to maximize the target of achieving successful education and teaching systems for children in accordance with the vision-mission and goals of education in park Kindergarten Mother Earth Dharma Wanita Palenga'an Pamekasan, East Java